Modeling the Impact of Corruption, Degree of Freedom to Invest and Democracy on Domestic Investment: Evidence from MENA Countries - Bakari, Sayef; Benzid, Lamia (Studies and Scientific Researches. Economics Edition, 2021)
This study examines the impact of corruption, investment freedom, and democracy on domestic investment in countries in the Middle East and North Africa. In order to achieve this, the GMM model was used to test the annual data from 2011 to 2017. The empirical results show that corruption has a negative impact on domestic investment, but the degree of investment freedom and democracy have a positive impact on domestic investment. One of the major contributions of this work is to assert the requirement to wheel more awareness to the direct link between corruption, governance, investment freedom, and domestic investment.